1988
DOI: 10.1002/jor.1100060512
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of epiphyseal cartilage collagenase by tetracyclines in low phosphate rickets in rats

Abstract: Drugs in the tetracycline family can inhibit mammalian tissue collagenase both in vitro and in vivo by a mechanism that is independent of antibiotic action. The epiphyseal cartilages of rachitic rats contain extremely high levels of collagenase (CGase), and we have used this model to study further the phenomenon of tetracycline inhibition of tissue CGase. Rickets was induced in rats by phosphate/vitamin D deficiency and parameters of gross bone morphology, bone chemistry, and serum chemistry were evaluated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…[13][14][15][16][17][18] The mechanisms by which doxycycline inhibits the MMPs are not completely understood. Doxycycline binds directly to Zn 2+ or Ca 2+ associated with the enzyme, resulting in blocking the active site or inducing conformational changes that render the proenzyme susceptible to fragmentation during activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18] The mechanisms by which doxycycline inhibits the MMPs are not completely understood. Doxycycline binds directly to Zn 2+ or Ca 2+ associated with the enzyme, resulting in blocking the active site or inducing conformational changes that render the proenzyme susceptible to fragmentation during activation.…”
Section: Discussionmentioning
confidence: 99%
“…13 Doxycycline and other derivatives of tetracycline are potent MMP inhibitors. [14][15][16][17][18] Inhibition of MMPs by doxycycline occurs independently of antimicrobial activity. The beneficial effect of doxycycline on ECM degradation in animal models and human beings has been attributed to the inhibition of MMPs.…”
mentioning
confidence: 99%
“…99 In vivo studies are also beginning to address the clinical potential in bone disorders of these tetracycline effects and to identify altemative mechanisms of tetracycline-reduced bone loss. Greenwald et al 39 reported that tetracyclines orally administered to rats with experimental rickets reduced the excessive collagenase activity in the epiphyseal growth plate, an effect that was associated with a partial normalization of the impaired growth and mineralization characteristic of this metabolic bone disease. The diabetic rat model continues to provide major new insights.…”
Section: Proanabolic As Well As Anticatabolic Activity Of Tetracymentioning
confidence: 97%
“…Tetracyclines inhibit the activity of neutral matrix metalloproteinases (MMPs) (1)(2)(3). This effect has been believed to be due, at least in part, to chelation of zinc and/or calcium (1,4), which maintain the normal structural conformation and hydrolytic activity of the MMPs (5).…”
mentioning
confidence: 99%